Pengembangan Fitur Dashboard dan Report pada Aplikasi Project Management PT Intelix untuk Optimalisasi Pemantauan Proyek - Afif Lukmanul Hakim; Hendra Pradibta (International Forum of Researchers and Lecturers, 2025)
PT Intelix, a technology and information company with numerous collaborative projects, faces challenges in effective project management and monitoring. Despite utilizing project management applications like Jira, the generation of final reports often remains a manual process using Microsoft Excel, which is time-consuming and prone to errors. To address these issues, PT Intelix developed an internal Project Management application, yet it required further enhancements in its dashboard and reporting features for more detailed project monitoring optimization. This research aims to develop the Dashboard menu by adding a priority project table and several sub-menus in the Report menu to accelerate and simplify the preparation of final project reports. The development methodology employed is Agile Kanban, encompassing planning, system and interface design, incremental development and implementation, and testing. System functionality testing was conducted using Black Box Testing and User Acceptance Test (UAT) involving the project owner and end-users from PT Intelix. Test results showed all main functions running smoothly and stably, with all black box scenarios passing. UAT testing on six menus received a